Alternate electrode placement for whole body and segmental bioimpedance spectroscopy - Grisbrook, Tiffany; Kenworthy, P.; Phillips, M.; Gittings, P.; Wood, F.; Edgar, D. (2015)
Bioimpedance spectroscopy (BIS) is frequently used to monitor body fluid and body composition in healthy and clinical populations. BIS guidelines state that there should be no skin lesions at the site of electrodes, and if lesions are present, electrode positions should be changed. However, alternate electrode positions are yet to be reported. This study aimed to determine if ventral electrode placements were suitable alternatives for whole body and segmental BIS measurements. Three alternate electrode placements were assessed for whole body BIS using a combination of ventral hand and foot electrode placements. An alternate position was assessed for upper and lower body segmental BIS. The results demonstrated that for whole body BIS, if drive and sense electrodes on the hand are moved to ventral positions, but foot electrodes remain in standard positions, then whole body BIS variables were comparable to standard electrode positioning (percentage difference range=0.01 to 1.65%, p=0.211–0.937). The alternate electrode placement for upper limb segmental BIS, results in BIS variables that are comparable to that of the standard positioning (percentage difference range=0.24–3.51%, p=0.393–0.604). The alternate lower limb electrode position significantly altered all resistance and predicted BIS variables for whole body and lower limb segmental BIS (percentage difference range=1.06–12.09%, p<0.001). If wounds are present on the hands and/or wrist, then the alternate electrode position described in this study is valid, for whole body and upper limb segmental BIS.